(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Human resource management (HRM) additionally alludes to the structure of formal frameworks in an organization to guarantee the viable and proficient utilization of human abilities to achieve the organizational objectives without yielding the requirements of the organizational human components. Employee retention has turned into a basic issue and a basic subject on numerous grounds. Employee retention is an essential issue and a test looked by the greater part of the organizations now-a-days. There are number of factors which elevate employees to remain or leave the organization. These might be outside factors, inside factors or the joined impact of both. The Automobile industry assumes a huge job in the supporting of monetary development of the nation. The examination closed the requirement for employee retention of Automobile Industries in India, and presumes that there are different factors specifically job satisfaction, rewards, training and development, career development have more noteworthy effect on employee retention. The primary aim of this paper is to determine the after- effects on employee retention and study the relationship of employee retention with job security and work life balance. Job security proved the most important factor for retention of employees among all others factors. It encourages employee’s decision to remain with the organization. It is found in the study that Work life balance has strong and positive correlation with Employee’s retention